Effect of Activated Bentonite Concentration on the Characteristics of Virgin Coconut Oil (VCO) via Enzymatic Method (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2025)
This study aimed to evaluate the effectiveness of activated bentonite in improving the quality of Virgin Coconut Oil (VCO). The quality of VCO is strongly influenced by moisture content, free fatty acids, and peroxide value. In this study, VCO was produced using an enzymatic method with papain and then purified using activated bentonite at concentrations of 3%, 5%, and 10%. The quality parameters analyzed included moisture content, free fatty acids (FFA), peroxide value, specific gravity, viscosity, and organoleptic attributes such as aroma, color, and taste. The results showed that 10% activated bentonite provided the best performance, with FFA at 0.174%, peroxide value at 0.99 mEq/kg, specific gravity at 0.4524 g/mL, moisture content at 0.0026%, and viscosity at 10.47 cP. Organoleptic tests indicated improvement in aroma, color, and taste. Therefore, the use of activated bentonite has been proven effective in enhancing the quality characteristics of VCO in accordance with the Indonesian National Standard (SNI).